2011
DOI: 10.1038/mt.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Therapy With JX-594, A Targeted Oncolytic Poxvirus, Followed by Sorafenib in Hepatocellular Carcinoma: Preclinical and Clinical Demonstration of Combination Efficacy

Abstract: JX-594 is a targeted and granulocyte-macrophage colony stimulating factor (GM-CSF) expressing oncolytic poxvirus designed to selectively replicate in and destroy cancer cells through viral oncolysis and tumor-specific immunity. In a phase 1 trial, JX-594 injection into hepatocellular carcinoma (HCC) was well-tolerated and associated with viral replication, decreased tumor perfusion, and tumor necrosis. We hypothesized that JX-594 and sorafenib, a small molecule inhibitor of B-raf and vascular endothelial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 31 publications
2
104
0
Order By: Relevance
“…In addition to the role played by OV-induced inflammation, JX-594 has been shown to directly infect and kill tumourassociated vascular endothelial cells in mice following intravenous (IV) delivery (Breitbach et al, 2013). These findings have been confirmed in human HCC trials, demonstrating disruption of tumour perfusion following JX-594 therapy Heo et al, 2011).…”
Section: A H Jebar and Otherssupporting
confidence: 58%
“…In addition to the role played by OV-induced inflammation, JX-594 has been shown to directly infect and kill tumourassociated vascular endothelial cells in mice following intravenous (IV) delivery (Breitbach et al, 2013). These findings have been confirmed in human HCC trials, demonstrating disruption of tumour perfusion following JX-594 therapy Heo et al, 2011).…”
Section: A H Jebar and Otherssupporting
confidence: 58%
“…Clinically, profound tumor vascular ablation and subsequent durable tumor necrosis and long-term survival have been induced by JX-594 followed by small-molecule inhibitors of VEGFR in hypervascular HCC and renal cell cancers (both VEGF-rich; ref. 44). Of note, this potential synergy was reported even in patients who had failed previous therapy with sorafenib.…”
Section: Discussionmentioning
confidence: 98%
“…The virus, either alone or in combination with sorafenib, a small molecule inhibitor of B-Raf and vascular endothelial growth factor (VEGF) receptor, was well-tolerated and displayed objective tumor response in a small number of patients with hepatocellular carcinoma. 14 In a recent study, Breitbach et al showed in a clinical trial that JX-594 selectively infects, replicates, and expresses transgene products in cancer tissue after intravenous infusion in a dose-related fashion in human cancer patients. 15 China approved the world's first OV (H101) for cancer treatment in 2005, showcasing the potential of OVs as a new class of pharmaceutical drugs for cancer patients.…”
Section: Introductionmentioning
confidence: 99%